2013
DOI: 10.1039/c3cc46244g
|View full text |Cite
|
Sign up to set email alerts
|

Growth of a ZIF-8 membrane on the inner-surface of a ceramic hollow fiber via cycling precursors

Abstract: For the first time, a ZIF-8 membrane was grown on the inner surface of a ceramic hollow fiber via cycling precursors. The inner-side hollow fiber ZIF-8 membrane exhibits good performance for recovering hydrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(51 citation statements)
references
References 36 publications
1
48
1
1
Order By: Relevance
“…10. [14,15,[18][19][20][21]23,24,31,33,34,[37][38][39][41][42][43][44][45][46]. The Robeson upper bound is trade-off line of the polymeric gas separation membrane.…”
Section: Comparison Of the Separation Performancementioning
confidence: 99%
“…10. [14,15,[18][19][20][21]23,24,31,33,34,[37][38][39][41][42][43][44][45][46]. The Robeson upper bound is trade-off line of the polymeric gas separation membrane.…”
Section: Comparison Of the Separation Performancementioning
confidence: 99%
“…Recently, Brown et al reported a novel and scalable interfacial microfluidic processing approach for fabricating metal organic frameworks (MOFs) hollow fiber membranes [22]. In our previous work, highquality ceramic hollow fiber composite membranes were developed based on various kinds of materials, such as PDMS [23], ZIF-8 [24] and graphene oxide [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the last ve years, more and more effort has been paid to the preparation of ZIF-8 membranes by in situ growth, secondary growth, and also the liquid phase epitaxy method. [16][17][18][19][20][21][22][23][24][25]33 However, it was oen found that separate ZIF-8 crystals or islands rather than continuous layers were formed on the native ceramic supports by direct solvothermal synthetic routes because heterogeneous nucleation of ZIF-8 crystals on the support surfaces was very poor. 17,26 Therefore, seed coating 20,21 or chemical modication 17,26 of the supports have been applied to promote the heterogeneous nucleation of ZIF-8 crystals on support surfaces.…”
Section: Introductionmentioning
confidence: 99%